Extra virgin olive oil improves post-prandial glycemic and lipid profile in patients with impaired fasting glucose. Issue 3 (June 2017) - Carnevale, Roberto; Loffredo, Lorenzo; Del Ben, Maria; Angelico, Francesco; Nocella, Cristina; Petruccioli, Andreina; Bartimoccia, Simona; Monticolo, Roberto; Cava, Edda; Violi, Francesco
Summary: Background & aims: Extra virgin olive oil (EVOO) improves post-prandial glycaemia in healthy subjects but it has never been investigated if this can be detected in pre-diabetic patients. We investigated if EVOO affects post-prandial glucose and lipid profile in patients with impaired fasting glucose (IFG). Methods: Thirty IFG patients were randomly allocated to a meal containing or not 10 g of EVOO in a cross-over design. Before, 60 min and 120 min after lunch a blood sample was taken to measure glucose, insulin, Glucagon-like peptide-1 (GLP1), dipeptidyl-peptidase-4 (DPP4) activity, triglycerides (TG), total cholesterol, HDL-cholesterol and Apo B-48. Results: The meal containing EVOO was associated with a reduction of glucose (p = 0.009) and DPP4 activity (p < 0.001) and a significant increase of insulin (p < 0.001) and GLP-1 (p < 0.001) compared with the meal without EVOO. Furthermore, the meal containing EVOO showed a significant decrease of triglycerides (p = 0.002) and Apo B-48 (p = 0.002) compared with the meal without EVOO. Total cholesterol and HDL cholesterol levels did not significantly change between the two groups. Conclusions: This is the first study to show that in IFG patients EVOO improves post-prandial glucose and lipid profile with a mechanism probably related to incretin up-regulation.